Betamethasone causes intergenerational reproductive impairment in male rats - Borges, Cibele dos Santos [UNESP]; Pacheco, Taina Louise [UNESP]; da Silva, Katiussia Pinho [UNESP]; Fernandes, Fábio Henrique [UNESP]; Gregory, Mary; Pupo, André Sampaio [UNESP]; Salvadori, Daisy Maria F. [UNESP]; Cyr, Daniel G.; Kempinas, Wilma De G. [UNESP] (Elsevier, 2017)
Prenatal betamethasone (BM) exposure in rats negatively impacts sperm quality and male fertility. Studies have shown that BM can cause multi-generational effects on the pituitary-adrenal-axis of rats. The objective of this study was to assess the reproductive development and fertility of male rats (F2) whose fathers (F1) were exposed to BM (0.1 mg/kg) on gestational days 12, 13, 18 and 19. In F2 rats, there was a significant reduction in body weights of the BM-treated group at PND 1 as well as delayed onset of puberty, and decreases in FSH levels, Leydig cell volume, sperm number and motility, seminal vesicle contractility and ejaculated volume. Furthermore, increased serum LH levels, sperm DNA damage and abnormal morphology were observed, resulting in reduced fertility. In conclusion, prenatal BM-treatment leads to intergenerational long-term reproductive impairment in male rats, raising concern regarding the widespread use of BM in preterm births.
Keywords: Betamethasone intergenerational effects; Fertility; Puberty onset; Seminal vesicle contractility; Sperm quality